Effects of physical training in a hypobaric chamber on the physical performance of competitive triathletes - Vallier, J. M.; Chateau, P.; Guezennec, C. Y. (European Journal of Applied Physiology, 1996)
The effects of training in a hypobaric chamber on aerobic metabolism were studied in five high performance triathletes. During 3 weeks, the subjects modified their usual training schedule (approximately 30 h a week), replacing three sessions of bicycling exercise by three sessions on a cycle ergometer in a hypobaric chamber simulating an altitude of 4,000 m (462 mm Hg). Prior to and after training in the hypobaric chamber the triathletes performed maximal and submaximal exercise in normoxia and hypoxia (462 mm g). Respiratory and cardiac parameters were recorded during exercise. Lactacidaemia was measured during maximal exercise. Blood samples were drawn once a week to monitor blood cell parameters and erythropoetin concentrations. Training in the hypobaric chamber had no effect on erythropoiesis, the concentrations of erythropoetin always remaining unchanged, and no effect on the maximal oxygen uptake (VO2max) and maximal aerobic capacity measured in normoxia or hypoxia. Submaximal performance increased by 34% during a submaximal exhausting exercise performed at a simulated altitude of 2,000 m. During a submaximal nonexhausting test, ventilation values tended to decrease for similar exercise intensities after training in hypoxia. The changes in these parameters and the improved performance found for submaximal exercise may have been the result of changes taking place in muscle tissue or the result of training the respiratory muscles.